(untitled) (Proceedings of the International Conference on Public Health, 2019)
As an increase in overloaded general hospitals in Vietnam, nurses are under intensive pressure but receive little opportunities for learning new technical skills and for developing an obvious career path. Meanwhile, nurse performance is essential to quality outcomes of healthcare services. Therefore, this study aims to investigate primary drivers of nurse performance by using the structural equation model approach to analyze a survey of 366 nurses working in four hospitals in Ho Chi Minh City and Bac Lieu province, Vietnam. The results show the facilitating effects of affective commitment and self-leadership on job performance, but not continuance commitment and communication competence. Also, the empirical evidence supports that perceived organizational support and psychological safety indirectly impact job performance through affective commitment. Job resources, however, are insignificantly related to affective commitment. The study indicated that nurses with a high degree of self-leadership and affective commitment to the organization are prone to attain high job performance. Therefore, managers should implement strategies to enhance nurses’ conception of self-leadership and affective commitment, which would be an efficient approach to improve quality healthcare services. This study also makes some explanations for the divergence between the previous literature on factors affecting nurse performance and that in Vietnamese hospital context.